ELECTRICITY TOKEN VALUE BUTTON PRESSING SYSTEM ON HELPED PREPAID ELECTRICITY KWh METER BLUETOOTH USING MIT APP INVENTOR - Kartika; Mhd Agung Asmara; Misriana (PT. Radja Intercontinental Publishing, 2023)
The system of pressing the electricity token value button on the prepaid electricity kWh meter is a tool that works by filling in the electricity token value via smartphone with the MIT APP Inventor server which aims to make it easier for prepaid electricity users by not having direct contact with the prepaid kWh meter. In general, filling in the value of electricity tokens is still done manually and what happens is that there are still many people who experience problems with distance and are afraid to top up the value of electricity tokens manually. This research aims to create a control system for pressing keypad buttons on prepaid kWh meters. The control system uses Arduino Uno with the MIT APP Inventor server as input from the smartphone. Data sent from the smartphone will be received by the Bluetooth Module which is processed by the Arduino Uno as a microcontroller to control the relay driver as a selonoid controller, the selonoid as a button press will work by inputting the electrical token value that has been input. The research results show that a system of pressing the electricity token value button on the prepaid electricity kWh meter has been realized. Testing is carried out by operating and testing the tool functionally and the performance of all components as well as realizing that the tool is successful and the tool works as expected.